Incidence and Mortality by the Main Types of Cancer in the City of Cuiabá, Mato Grosso, Between the Years of 2008 and 2016 - Jânia Cristiane de Souza Oliveira; Lucas Matos Castelo; Mariana Rosa Soares; Amanda Silva Magalhães; Danielle Martins da Costa Eustáquio; Jacqueline Pimenta Navarro-Silva; Bárbara da Silva Nalin de Souza; Noemi Dreyer Galvão; Amanda Cristina de Souza Andrade (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2022)
ABSTRACT: Objective: To analyze the temporal trend of the incidence and mortality rate for prostate, breast, colorectal, lung, cervical, stomach and laryngeal cancer among residents in the city of Cuiabá between 2008 and 2016. Methods: Time series study with data from the Mortality Information System and the Population-Based Cancer Registry. Stratified by sex, the proportional distribution of new cases and deaths by age group and the cancer incidence and mortality rates standardized by the world population were calculated. Linear regression was used and the annual percentage change (APC) was estimated. Results: In males, most new cases and deaths, for the main types of cancer, occurred among those aged 50 years or older, and the incidence rate of prostate cancer showed a tendency to decrease in the period (APC=-4.33%). For females, the proportion of new cases and deaths, due to breast and cervical cancer, were more frequent among women aged 50 years or younger, and lung, stomach and colorectal cancer among women aged 50 years or older. The incidence rate of breast cancer showed an increasing trend (APC=3.60%). For both sexes, the mortality rate remained stable. Conclusion: The incidence rate trend varied between sexes, an increase was observed for breast cancer among women and a reduction for prostate cancer among men. The mortality rate for the main types of cancer was stable.